1999
DOI: 10.1149/1.1391910
|View full text |Cite
|
Sign up to set email alerts
|

Topological Analysis of the Electron Localization Function: A Help for Understanding the Complex Structure of Cryolitic Melts

Abstract: A theoretical study of the solvated AlF63− , AlF52− , and AlF4− species which are involved in cryolitic melts was performed. Based on the density functional theory formalism, a structural and vibrational analysis of these isolated molecules was carried out, allowing determination of their relative stabilities. A further topological analysis of the electron localization function gradient field reveals this to be a powerful tool to provide insight into the bonding properties of these molecules. The dative‐po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recent theoretical studies are relevant. It has been shown in several reports that cations can stabilize both five- and six- coordinated fluoroaluminates. Joubert and co-workers 48 have calculated the most stable configurations for the cluster of 3 Na + Al + 6 F (i.e., cryolite, Na 3 AlF 6 ). These authors performed their calculations at a very high level using density functional theory (DFT) combined with topological analysis of the electron localization function (ELF) gradient field.…”
Section: Resultsmentioning
confidence: 99%
“…Recent theoretical studies are relevant. It has been shown in several reports that cations can stabilize both five- and six- coordinated fluoroaluminates. Joubert and co-workers 48 have calculated the most stable configurations for the cluster of 3 Na + Al + 6 F (i.e., cryolite, Na 3 AlF 6 ). These authors performed their calculations at a very high level using density functional theory (DFT) combined with topological analysis of the electron localization function (ELF) gradient field.…”
Section: Resultsmentioning
confidence: 99%
“…In many quantum-chemical studies a basic approach is to calculate the parameters of model systems containing an anionic complex with an OS cationic shell (e.g. [14][15][16][17][31][32][33][34]. For similar systems nM + ⋅[NbF 7 ], nM + ⋅[CrCl 6 ] (n = 1n max ) and others, it has been demonstrated that the most thermodynamically stable compositions have some intermediate number of OS cations n < n max , where n max is the maximal number of OS cations held by a given complex.…”
Section: Quantum-chemical Calculationsmentioning
confidence: 99%
“…As can be seen from Quantum-chemical calculations.-In many quantum-chemical studies, a basic approach is to calculate the parameters of model systems containing an anionic complex with an OS cationic shell (e.g. [14][15][16][17][33][34][35][36]. For similar systems nM + •[NbF 7 ], nM + •[CrCl 6 ] (n = 1n max ) and others, it has been demonstrated that the most thermodynamically stable compositions have some intermediate number of OS cations n < n max , where n max is the maximal number of OS cations held by a given complex.…”
Section: Determination Of the Standard Rate Constants Of Charge-trans...mentioning
confidence: 99%